Studies on the Interaction between Collagen and a Plasma Kallikrein-Like Activity EVIDENCE FOR A SURFACE-ACTIVE ENZYME SYSTEM - Harpel, Peter C. (1972)
This study has demonstrated that collagen particles, after exposure to platelet-poor human plasma and subsequent washing, generate a kinin-like agent when incubated with prekinin substrate. The binding of kinin-generating activity to collagen in the plasma collagen incubation mixture occurs rapidly, whereas the loss of this activity in the incubation mixture occurs relatively slowly. The Hageman factor appeared to be necessary for the surface-bound kinin-generating activity, as this activity was absent in collagen exposed to Hageman factor-deficient plasma. These studies have partially characterized the plasma-derived enzymatic activity bound to collagen. Incubation of collagen with plasma caused a concentration-dependent reduction in the kinin-producing activity which was generated by the addition of ellagic acid, a known activator of plasma kallikrein. The kinin-inducing activity bound to collagen is inhibited by soybean trypsin inhibitor, Trasylol, serum C1̄ inactivator and the plasma α(2)-macroglobulin, but not by lima bean trypsin inhibitor. An eluate prepared from plasma-treated collagen, when compared with purified plasma kallikrein, shared a similar inhibitor profile. Selective chemical blockage of the free carboxyl groups on the collagen molecule, or heat denaturation, inactivated the ability of the collagen to generate kinin-like activity after incubation with plasma. Removal of the collagen telopeptides or blockage of the free amino groups failed to affect the collagen-plasma interaction. The binding of partially purified plasma kallikrein to collagen was found to have similar structural and chemical requirements. These data indicate that there is a structural and chemical specificity for the activation and binding of plasma kallikrein-like activity by collagen. These studies suggest that a plasma kallikrein may function as a surface-bound enzyme system.